Fragmenting the family? The complexity of household migration strategies in post-apartheid South Africa - Katharine Hall; Dorrit Posel (IZA Journal of Development and Migration, 2019)
The disruption of family life is one of the important legacies of South Africa's colonial and apartheid history. Families were undermined by deliberate strategies implemented through the pass laws, forced removals, urban housing policy, and the creation of homelands. Despite the removal of legal restrictions on permanent urban settlement and family co-residence for Africans, patterns of internal and oscillating labor migration have endured, dual or stretched households continue to link urban and rural nodes, children have remained less urbanized than adults, and many grow up without coresident parents. Although children are clearly affected by adult labor migration, they have tended to be ignored in the migration discourse. In this study, we add to the literature by showing how a child lens advances our understanding of the complexities of household arrangements and migration processes for families. In a mixed-methods study, we use nationally representative panel data to describe persistence, and also change, in migration patterns in South Africa when viewed from the perspective of children. We then draw on a detailed case study to explore what factors constrain or permit families to migrate together, or children to join adults at migration destination areas.
Keywords: O15; J13; 330; children; family migration; household strategies; mixed methods; South Africa